Quality of Life and its associated factors among caregivers of patients with dementia – A cross-sectional study in Kuching, Sarawak, Malaysia - Ivan Vun, JS; Cheah, WL; Helmy, H. (2020)
This study aimed to determine the quality of life and its associated factors among caregivers of patients with dementia in Kuching, Sarawak, Malaysia. Methods: This cross-sectional study was carried out among caregivers for dementia patients who visited three main hospitals in Kuching, Sarawak. Using a validated questionnaire, data was obtained based on socio-demographic profile, patient and caregiving characteristics, supports needs by caregivers, and quality of life (QoL) of caregivers modified from Zarit Burden Interview (ZBI), Hospital Anxiety and Depression Scale (HADS) and Evaluation’s Scale of the Caregiver’s QoL. Results: A total of 217 caregivers participated with response rate of 99.6%, with 67.3% female and 63.1% Chinese. Most respondent provide care for their parents (62.7%), and stay with patients (67.3%). Average duration of care was 4.2 years (SD±3.72). Resource referral (M=3.52, SD±1.334) and education support (M=3.67, SD±1.054) was highest need. Majority respondents experienced little to no burden (59%). Most respondents were not depressed (98.1%). The QoL of respondents was satisfactory (M=41.36, SD±25.840). Gender of caregivers, patients with behavioural and psychological symptoms of dementia, duration of caregiving, respite care need, caregiver disability or illness, belonging support need, education support need were significantly associated with QoL of caregivers (p<0.05). Conclusion: This study on QoL of caregivers of dementia patients in Sarawak, Malaysia shows that it can be influenced by many factors, both at the caregivers’ level as well as the patients themselves. Therefore, intervention should aim at patients and their caregivers, and within community and healthcare settings.